The role of pendrin in health and disease : molecular and functional aspects of the SLC26A4 anion exchanger - Dossena, Silvia; Paulmichl, Markus (Springer, 2017)
This book reviews the current state of knowledge on the genetics, molecular biology and physiology of pendrin, with a particular focus on pendrin dysfunction and the consequences for human health. Pendrin is a membrane transport protein expressed in the thyroid, inner ear, kidney and airways, and was recently found in a variety of other tissues and organs. Pendrin malfunction may cause a genetic disease called Pendred syndrome or non-syndromic deafness. The book provides a thorough description of the multifaceted role of pendrin in human health and disease. As such, it offers an invaluable tool for physiology and pathology researchers, while also providing essential guidance for otorhinolaryngologists and endocrinologists in the diagnosis of Pendred syndrome and pendrin-related deafness.- Resumé vydavatel
Includes index.
Keywords: membránové bílkoviny; buněčné membrány; biochemie; membrane proteins; cell membranes; biochemistry; elektronické knihy; sborníky; electronic books; papers of several authors